Income Analysis Of The Tofu Industry In Sugihwaras Village, Wonomulyo Sub-District - Qadri, Syarif Al-; Hikma, Aulia Nurul; Hamsah, Hamsah (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the income levels and the influencing factors of tofu enterprises in Sugihwaras Village, Wonomulyo Sub-district, Polewali Mandar Regency. The tofu industry represents a form of household-scale enterprise that continues to thrive amid the dynamic rural economy. This research employs a descriptive quantitative approach, utilizing data collection techniques such as observation, questionnaires, and documentation from 15 tofu business owners. The results show that the average net income of tofu entrepreneurs is IDR 9,149,655 per month, with a total production cost of IDR 140,220,345 and total revenue of IDR 149,370,000. The main factors influencing income include fluctuations in the price of raw materials (soybeans), efficient use of family labor, and traditional marketing strategies. Despite its modest operations, this industry significantly contributes to household economies and has potential for development through the application of simple technologies and managerial strengthening. This study is expected to serve as a basis for policy formulation aimed at strengthening local food MSMEs in rural areas..